PENGEMBANGAN E-MODUL BERBASIS FLIPBOOK UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA SMP TEMA CAHAYA - Heny Sholikhatul Awwaliyah; Rina Rahayu; Ahmad Muhlisin (Universitas Tidar, 2021)
The study aims to analyze the worthiness, the effectiveness, and the practical science e-module flipbook-based as the learning material to improve students’ learning motivation in light topic and its benefits for life. The writer decided to develop teaching material to support online class such as e-module flipbook-based. This study is research and development (R&D) using ADDIE model. This study used Likert Scale with particular interval as data analysis technique. To know the worthiness of the data, the writer used validation sheets which had been validated by e-module expert and material expert and its result is categorized as worthy. Then, the effectiveness of the data used motivation questionnaires which are given before and after the learning process. The practical level had been done from the questionnaire of students and teachers’ response. The results of this study showed that e-module can be categorized as worthy, effective, and practical to use. Therefore, it can be concluded that the development of e-module flipbook-based to improve students’ learning motivation achieves the expected objectives and help the teachers as a reference in developing an interesting learning material for students to improve their learning motivation when they do online class.